Engaging target users to appraise and refine clinical practice guidelines in pediatric concussion: An integrated knowledge translation approach. (May 2021) - Paniccia, Melissa; Provvidenza, Christine; Kingsnorth, Shauna; Ippolito, Christina; Zemek, Roger; Reed, Nick
Background: Clinical practice guidelines are systematically developed statements that assist clinicians in making evidence informed decisions regarding patient care. Within pediatric concussion, the Ontario Neurotrauma Foundation released the Guidelines for Diagnosing and Managing Pediatric Concussion in 2014. The purpose of this study was to evaluate the 2014 guidelines using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) evaluation tool, in addition to a brief knowledge translation survey, and to utilize the collected feedback from end users to inform improvements to support an updated version. An integrated knowledge translation approach was employed using clinical experts as guideline appraisers. Methods: A purposive sample of researchers, physicians, allied health professionals, policy makers, educators and knowledge translation experts involved in updating the guidelines (N = 31) completed the AGREE II Likert scale survey regarding the 2014 guideline, and provided written justifications for their ratings. Domain and item AGREE II scaled scores were reported stratified by demographic factors, and written justifications were synthesized using content analysis to determine areas of improvement for the 2014 guideline. Results: Appraisers scored the editorial independence (88.9%) and scope and purpose (80.8%) domains the highest, indicating high quality. The guidelines scored the lowest in the applicability domain (69.3%). Participants with less than 10 years of experience in their respective disciplines, as well as physicians and allied health professionals consistently provided higher ratings across domains compared to other professions. Conclusions: The process of evaluating the 2014 guideline resulted in these important outcomes: (1) identified areas of the guideline that may have affected the lack of previous clinical uptake while abiding by a clinical practice guideline development framework; (2) shared and informed decision making regarding content and format of the revised clinical practice guideline; and (3) targeted content, clinical questions and dissemination strategies, which are key to clinical uptake.